2011
DOI: 10.1039/c0sm01004a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular motors stiffen non-affine semiflexible polymer networks

Abstract: Reconstituted filamentous actin networks with myosin motor proteins form active gels, in which motor proteins generate forces that drive the network far from equilibrium. This motor activity can also strongly affect the network elasticity; experiments have shown a dramatic stiffening in in vitro networks with molecular motors. Here we study the effects of motor generated forces on the mechanics of simulated 2D networks of athermal stiff filaments. We show how heterogeneous internal motor stresses can lead to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(125 citation statements)
references
References 38 publications
(149 reference statements)
5
119
0
1
Order By: Relevance
“…Future work can be aimed at elucidating the individual roles of fiber properties (e.g., d, L, l p , and E) and cross-linker properties (e.g., k cl and r 0 ), which will enable more quantitative comparison to other experimental and theoretical works. 22,24,28,51 These properties, or the distribution thereof, 21,52,53 are likely to affect the structural network response by varying the length-scale difference between the heterogeneous and the homogeneous scales.…”
Section: Discussionmentioning
confidence: 99%
“…Future work can be aimed at elucidating the individual roles of fiber properties (e.g., d, L, l p , and E) and cross-linker properties (e.g., k cl and r 0 ), which will enable more quantitative comparison to other experimental and theoretical works. 22,24,28,51 These properties, or the distribution thereof, 21,52,53 are likely to affect the structural network response by varying the length-scale difference between the heterogeneous and the homogeneous scales.…”
Section: Discussionmentioning
confidence: 99%
“…In fact forκ 10 −3 , the critical strain obtained in this way is practically constant. Moreover, the range of 10 −5 κ 10 −3 is the experimentally relevant range [24,33]. In particular, the central-force limit is not achievable experimentally.…”
Section: Strain Driven Criticalitymentioning
confidence: 99%
“…Fibers are arranged on a triangular lattice (2D) or a facecentered cubic lattice (3D) of linear dimension W . In 2D, we randomly select two of the three fibers at each vertex on which we form a binary cross-link, i.e., enforcing local fourfold connectivity of the network in which the third fiber does not interact with the other two [24]. Similarly, in 3D, where there are six fibers crossing at a point, we randomly connect three separate pairs of fibers at each vertex with binary cross-links to enforce local fourfold connectivity [25].…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond this, theoretical work has shown that there are numerous ways of stabilizing a network, and therefore tuning its rigidity, below the isostatic point [15]. Examples include the addition of a bending stiffness to the model filaments [16][17][18] by applying stress [19] either internally via molecular motors [20,21] or externally by placing the network under tension by applying a bulk strain to the system [22][23][24]. It has been shown that a network's rigidity point can be shifted from the Maxwell point by adding these interactions and forces to the system.…”
Section: Introductionmentioning
confidence: 99%